Environmental quality and ecotoxicity of sediments from the lower Salado River basin (Santa Fe, Argentina) on amphibian larvae - Peluso, Julieta (2022)
The lower Salado River basin receive agricultural, industrial and domestic waste water. So, the aim was to evaluate the quality of three sampling sites that belong to the Salado River basin (S1: Cululú stream; S2: Salado River, at Esperanza City, S3: Salado River at Santo Tomé City) based on physicochemical parameters, metals and pesticides analyses and ecotoxicity on Rhinella arenarum larvae. R. arenarum larvae (Gosner Stage -GS- 25) were chronically exposed (504h) to complex matrixes of surface water and sediment samples of each site for the determination of the survival rate. Biomarkers of oxidative stress, neurotoxicity and genotoxicity were analyzed in R. arenarum larvae (GS. 25) after exposure (96h) to the complex matrix of water and sediment. The water quality index showed a marginal quality for all sites, influenced mainly by low dissolved oxygen, high total suspended solid, phosphate, nitrite, conductivity, Pb, Cr and Cu levels. Metal concentrations were higher in sediment than in water samples (˜34-35000 times). In total, thirty different pesticides were detected in all water and sediment samples, S1 presented the greatest variety (26). Glyphosate and AMPA were detected in sediments from all sites, being higher in S3. N,N-Diethyl-meta-toluamide (DEET) and atrazine were detected in all water samples. Greatest mortality was observed in larvae exposed to samples from S1 from 288h (43.3%), reaching a maximum value of 50% at 408h. Oxidative stress and genotoxicity were observed in larvae exposed to S1 and S3 matrix samples. Neurotoxicity was observed in larvae exposed to all matrix samples. The integrated biomarker response index showed that larvae exposed to S1 and S3 were the most affected. According to the physicochemical data and the ecotoxicity assessment, this important river basin is significantly degraded and may represent a risk to aquatic biota, especially for R. arenarum larvae.